Discovery of a series of 2-(pyridinyl)pyrimidines as potent antagonists of GPR401. Issue 6 (10th June 2015) - Waring, Michael J.; Baker, David J.; Bennett, Stuart N. L.; Dossetter, Alexander G.; Fenwick, Mark; Garcia, Rob; Georgsson, Jennie; Groombridge, Sam D.; Loxham, Susan; MacFaul, Philip A.; Maskill, Katie G.; Morgan, David; et al.
<x xml:space="preserve">Abstract</x> A series of 2-(pyridinyl)pyrimidines were identified as potent GPR40 antagonists.